Limbah Sabut Kelapa Muda (Cocos nucifera L.) sebagai Sumber Pewarna Kain: Young Coconut Coir (Cocos nucifera L.) Waste as a Source of Cloth Dye - Ni Ketut Sumarni; Umma Fahriah Soleh; Nurhaeni; Prismawiryanti (KOVALEN: Jurnal Riset Kimia, 2021)
Young coconut coir (Cocos nucifera Linn.) waste has the potential to be processed into a useful product, namely as a source of natural dyes, especially in cotton fabrics. Processing is carried out through a maceration process for 72 hours using 96% ethanol as solvent. The obtained extract was applied on cotton cloth with various concentrations of the extract solution, 5, 10, 15, 20, and 25%, and various soaking times of the fabric in the extract for 60, 90, 120, 150, and 180 minutes. The extract was analyzed using Uv-Vis Spekctrofotometer it showed that the ethanol extract or dye that is absorbed into the cotton fabric with various concentrations is 3.43, 4.82, 6.61, 7.79, and 9.03%, respectively. The various soaking times show that on the other hand that the extract absorbed into the fabric was successfully obtained around 7.75, 9.64, 10.81, 11.65, and 12.04%. The results show that the concentration of the extract solution and the increasing length of soaking time can increase the percentage of extract or dye absorbed in cotton fabrics